Refuting the Epistemic Supremacy of Orientalism in Islamic Law: a Postcolonial Theoretical Perspective - Ilham Tohari; Zayad Abd. Rahman; Aminatur Rosidah; Umar Wismohadi Pranoto; Miftahul Choriyah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
This article examines the epistemic architecture that Orientalism has long employed to assert its intellectual supremacy over the study of Islamic law, thereby producing a hierarchy of knowledge that places sharia in a position of methodological inferiority and historical stagnation. This study demonstrates how colonial genealogy, representational bias, and disciplinary asymmetry have shaped the dominant interpretation of Islamic law within the global academic discourse. Drawing on insights from Said, Asad, Bhabha, and Santos, this analysis uncovers the mechanisms of epistemic distortion, epistemicide, and hermeneutic constraints that have limited the autonomy of Islamic legal reasoning. This study adopts a library-based qualitative design that conducts an in-depth examination of how knowledge about Islam has historically been constructed, distorted, and exploited within asymmetrical power structures. such as Scopus, Web of Science, and JSTOR. Data analysis employs a three-part strategy. First, Critical Discourse Analysis (CDA). Second, this study applies a postcolonial reading strategy to uncover acts of representation, silencing, and epistemic domination. Third, the method of comparative hermeneutics This finding underscores the need to formulate an epistemology of Islamic law that is free from colonialism—one that re-establishes uṣūl al-fiqh as a dynamic intellectual tradition, prioritizes maqāṣid al-sharīʿa as the teleological horizon for legal renewal, and embraces epistemic plurality as an antidote to Eurocentric universalism.